Les maïs natifs du nord, centre et sud du Mexique - Elena Lazos-Chavero; Michelle Chauvet (Revue d'ethnoécologie)
Maize landraces constitute the biocultural heritage of indigenous and mestizo peasants throughout the country. Its cultivation, conditioned by the climatic and agro-ecological environment, contributes to shape identities among communities. Maize is part of their food culture, of their historical legacy at the community level and of their shared meanings and symbols. The article discusses the alienable and inalienable characteristics of maize and the vulnerability of this binomial. The aim is to emphasize the importance of promoting maize biodiversity. This article traverses different agricultural mosaics between the north, south and center of the country in order to recognize that the entire national territory is the center of origin and diversification of maize. Finally, it warns about the risks of conceiving maize as a natural capital.